2018
DOI: 10.1093/infdis/jiy271
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Integrity Biomarkers in Early Antiretroviral-Treated Perinatally HIV-1–Infected Infants

Abstract: Intestinal fatty acid binding protein (iFABP) levels did not differ between human immunodeficiency virus type 1 (HIV-1)- infected infants and uninfected infants exposed to HIV-1, but those who breastfed had substantially lower levels. Zonulin levels increased from 3 to 5.3 months of age with perinatal acquisition of HIV-1 despite early antiretroviral treatment. Biomarkers of intestinal integrity (ie, iFABP and zonulin) were compared in 56 HIV-1-positive African infants who received early antiretroviral treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
3
13
1
Order By: Relevance
“…The correlation between delayed gastric emptying and elevated levels of IL‐10 is consistent with previous literature on IL‐10 and GI homeostasis, including gut barrier integrity and GI motility 33‐36 . An inverse relationship between IL‐10 and zonulin has also been previously reported, though not in critically ill patients 30,37 . Few studies have examined zonulin and gastric emptying or the relationship between IL‐10, zonulin, and gastric emptying, and results vary among existing studies 6,32,38,39 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The correlation between delayed gastric emptying and elevated levels of IL‐10 is consistent with previous literature on IL‐10 and GI homeostasis, including gut barrier integrity and GI motility 33‐36 . An inverse relationship between IL‐10 and zonulin has also been previously reported, though not in critically ill patients 30,37 . Few studies have examined zonulin and gastric emptying or the relationship between IL‐10, zonulin, and gastric emptying, and results vary among existing studies 6,32,38,39 .…”
Section: Discussionsupporting
confidence: 85%
“…Pediatric studies examining zonulin levels have not included critically ill patients and have focused on patients with chronic inflammatory conditions. [28][29][30] In addition to differences in the study population, our study examined zonulin at 2 time points, allowing for an assessment of zonulin under 2 conditions for the same patient, and found a decrease in zonulin postoperatively. Downregulation of zonulin has been reported and found to be associated with beneficial physiologic changes to the epithelial barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV infection, associated with high levels of pro-inflammatory cytokines, causes chronic immune activation, enhanced by HIV-induced gut disruption and dysbiosis [127,129]. Moreover, Persaud et al has demonstrated that IL-6 correlates with intestinal fatty acid binding protein-2 (IFABP2), a biomarker of intestinal damage, suggesting an association between inflammation and intestinal integrity [130]. Indeed, gut immunity and alterations are not fully restored by effective ART, leading to microbial translocation.…”
Section: Effects Of Hiv and Art Exposure On Inflammation Immunodymentioning
confidence: 99%